Innovative-growth accelerator management model - Stoyanova, Tsvetana (Leadership, Society, Strategic Visions, 2021)
Growth is the most important feature in the functioning of all modern business organizations and economies. It is the result of rapidly changing elements of the local, national and international socio-economic environment. The strength and direction of their impact to a certain extent depends on the specifi cs of the subject of activity and the target orientation of the enterprises. It is this impact that brings elements of uncertainty and instability to business development. In the last few decades, comprehensive methodologies and principles have been developed for the implementation of innovation in governance aimed at standardising good and effective practices so that they can be quickly and easily applied to different types of Organizations. In this publication, an attempt is made to justify the construction of an innovation accelerator leading to increased business growth.